(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The article presents research results on the effect of fruit and vegetable paste made from quince, apple, and pumpkin on the quality indicators of Turkish delight during a 40-day storage period. It has been proven that, during storage, the moisture content in the experimental samples of Turkish delight decreases less intensively, and the amount of reducing sugars increases to a lesser extent than in the control sample. This can be attributed to the higher fiber content, particularly pectin, in the experimental Turkish delight, which helps slow down the drying process and reduces the accumulation of reducing substances during storage. The acidity of the Turkish delight samples with added paste increases somewhat more slowly than in the control sample, and by the end of the storage period, it meets regulatory standards. The study of changes in water activity in Turkish delight with added fruit and vegetable paste during storage has shown that this indicator decreases more significantly than in the control sample. Meanwhile, the structural firmness of the experimental Turkish delight increased by 6.3%, while the control product increased by 12.0%. The reduction in water activity in the Turkish delight samples may be due to water loss, as well as stronger binding with non-starch polysaccharides compared to starch, which contributes to greater structural stability and less loss of firmness compared to Turkish delight without additives. After 40 days of storage, the organoleptic properties of products with added fruit and vegetable paste did not deteriorate significantly, with no foreign tastes or odors detected; only a slight weakening of the quince aroma and a less chewy consistency were observed. In contrast, products without additives showed a deterioration in taste, smell, and texture after 30 days of storage. This indicates the potential for producing more stable quality products and extending the shelf life of Turkish delight with added apple, quince, and pumpkin paste by 10 days.